Comparative Effectiveness of High-Dose vs. Standard-Dose Influenza Vaccines among Veterans: 2015–2016 and 2016–2017 Seasons. (4th October 2017) - Lucero-Obusan, Cynthia; Schirmer, Patricia; Wendelboe, Aaron; Ryono, Russell; Oda, Gina; Holodniy, Mark
Abstract: Background: Utilization of high-dose (HD) influenza vaccine in VA increased to 16% of all influenza vaccine given for 2016–17. HD vaccine is costlier than standard dose (SD) and no preferential recommendation has been made by the Advisory Committee on Immunization Practices. Herein, we evaluate the effectiveness of HD vs. SD vaccine for two influenza seasons. Methods: This retrospective cohort study identified patients receiving HD or SD influenza vaccines in all VA facilities using Current Procedural Terminology and Bar-Coded Medication Administration data from 8/1/2015–3/25/2017. Outcomes were laboratory-confirmed influenza and influenza-coded hospitalization >2 weeks after vaccine receipt. Sub-analysis was performed for patients ≥65 years at time of vaccination. Results: We evaluated 451, 899 HD and 3, 039, 743 SD vaccine recipients. The rate of laboratory-confirmed influenza was lower in the HD group for 2015–16 season (0.095% vs. 0.11%, P = 0.03) but not for the 2016–17 season. The rate of influenza hospitalization was lower among the SD group for 2016–17 (0.091% vs. 0.12%, P < 0.01), but was not different for the 2015–16 season. For patients ≥65 years there were no differences in rate of laboratory-confirmed influenza or influenza hospitalization for either season (Table). Conclusion: For the two seasons evaluated, HD vaccine was not found to be more effective than SD vaccine, particularly among patients ≥65 years, in reducing the occurrence of influenza or influenza-related hospitalizations. Disclosures: All authors: No reported disclosures.